Level of arterial ligation in sigmoid colon and rectal cancer surgery. Issue 1 (December 2016) - Yasuda, Koji; Kawai, Kazushige; Ishihara, Soichiro; Murono, Koji; Otani, Kensuke; Nishikawa, Takeshi; Tanaka, Toshiaki; Kiyomatsu, Tomomichi; Hata, Keisuke; Nozawa, Hiroaki; Yamaguchi, Hironori; Aoki, Shigeo; et al.
Abstract Background Curative resection of sigmoid colon and rectal cancer includes "high tie" of the inferior mesenteric artery (IMA). However, IMA ligation compromises blood flow to the anastomosis, which may increase the leakage rate, and it is unclear whether this confers a survival advantage. Accordingly, the IMA may be ligated at a point just below the origin of the left colic artery (LCA) "low tie" combined with lymph node dissection (LND) around the origin of the IMA (low tie with LND). However, no study has investigated the detailed prognostic results between "high tie" and "low tie with LND." The aim of this study was to assess the utility of "low tie with LND" on survival in patients with sigmoid colon or rectal cancer. Methods A total of 189 sigmoid colon or rectal cancer patients who underwent curative operation from 1997 to 2007 were enrolled in this study. The patient's medical records were reviewed to obtain clinicopathological information. Overall survival (OS) and relapse-free survival (RFS) rates were calculated using the Kaplan-Meier method, with differences assessed using log-rank test. Results Forty-two and 147 patients were ligated at the origin of the IMA (high tie) and just below the origin of the LCA combined with LND around the origin of the IMA (low tie with LND), respectively. No significant differences were observed in the complication rate and OS and RFS rates in the two groups. Further, no significant difference was observed in the OS and RFS rates in the lymph node-positive cases in the two groups. Conclusions "Low tie with LND" is anatomically less invasive and is not inferior to "high tie" with prognostic point of view.